Compensatory changes in energy balance regulation over one athletic season - Silva, A. M.; Matias, C. N.; Santos, D. A.; Thomas, D.; Bosy-Westphal, A.; Müller, M. J.; Heymsfield, S. B.; Sardinha, L. B. (Medicine & Science in Sports & Exercise, 2017)
Purpose: Mechanisms in energy balance (EB) regulation may include compensatory changes in energy intake (EI) and metabolic adaption (MA), but information is unavailable in athletes who often change EB components. We aim to investigate EB regulation compensatory mechanisms over one athletic season.